Astragaloside IV inhibits PMA-induced EPCR shedding through MAPKs and PKC pathway. (4th May 2017) - Ma, Yu; Zhao, Yi; Zhang, Ran; Liang, Xiaoxia; Yin, Zhongqiong; Geng, Yi; Shu, Gang; Song, Xu; Zou, Yuanfeng; Li, Lixia; Yin, Lizi; Yue, Guizhou; et al.
Abstract: Astragaloside IV (AS-IV), a main active substance isolated from Astragalus membranaceus Bunge, has been shown to have multiple pharmacological effects. Endothelial cell protein C receptor (EPCR) is a marker of inflammation, and is also a major member of protein C (PC) anti-coagulation system. EPCR can be cut off from the cell surface by tumor necrosis factor-α converting enzyme (TACE), which is controlled through mitogen-activated protein kinase (MAPK) and protein kinase C (PKC) pathways. To develop novel therapeutic drug for EPCR shedding, the effect of AS-IV was studied in phorbol-12-myristate 13-acetate (PMA)-induced human umbilical vein endothelial cells (HUVECs) and the potential molecular mechanism of AS-IV action was investigated. The results showed that AS-IV could significantly inhibit PMA-induced EPCR shedding. In further study, AS-IV suppressed the expression and activity of TACE. In addition, AS-IV could decrease the phosphorylation of MAPK such as janus kinase (JNK) and p38, and inhibit activation of PKC through the prevention of non-phosphorylation and phosphorylation of specific PKC isoforms in PMA-stimulated HUVECs. These findings indicate that AS-IV may be used as a natural medicine to treat EPCR-related systemic inflammation and cardiovascular diseases by targeting MAPK and PKC pathway.